Mepeed dan Wacana Ajeg Bali: Sukawati Pasca Bom Bali 2002 - Eka Ningtyas (Lembaran Sejarah, 2018)
This article endeavors to explore Ajeg Bali with special emphasis on mepeed ritual in traditional village of Pakraman Sukawati in post-Bali Bombing 2002. Analysis on this study focuses on how Ajeg Bali as a discourse could prompt changes occurred in Balinese society and how they shape Balinese identity. Firstly, this study tracks the advent of Ajeg Bali discourse by comparing practices of cultural preservation by Dutch colonial and New Order regime under Soeharto. Secondly, this study also observes position of Ajeg Bali discourse and how it affects society’s efforts to “protect” Bali. Thirdly, this article emphasizes on the mepeed ritual that transformed in Sukawati post-2002 especially in the spirit of Ajeg Bali. This study is a historical research that combines historical method and taking a cultural history point of view on explaining relation between mepeed and Ajeg Bali in Sukawati.